Romancing the other: Arundhati Roy’s The Ministry of Utmost Happiness - Lau, Lisa (2019)
Arundhati Roy’s second and latest novel, The Ministry of Utmost Happiness — which took her 10 years to write — is crammed full of misfits and outsiders, the flotsam and jetsam of India’s complex, stratified society. The novel is inhabited by cohorts of others: hijras, political rebels, the poor, women who will not “know their place”, and abandoned baby girls. The narrative of Roy’s latest political romance shows these others carving out new spaces for themselves, defying convention, trying possible new lives, and testing out new roles. This article aims to look at the texture of romance in Roy’s novels. Set within the narrative of Roy’s romance with India’s others, the article focuses on the Tilo–Musa romance in The Ministry of Utmost Happiness and compares it with the Ammu–Velutha romance in the author’s first novel, The God of Small Things, published in 1997. Romance in Roy’s novels serves multiple purposes, as this article argues and unpacks. Mapping out the patterns of romance which Roy creates in both her novels, this analysis employs the trope of romance as a lens through which to offer a postcolonial reading of The Ministry of Utmost Happiness, which interpenetrates intimacy and desire and the political. Deconstructing the (remarkably similar) romances at the heart of both of Roy’s novels reveals that her romances may not just be her rebuttal to India’s wrongs, but may even constitute a form of political rescue. We conclude that although Roy is purposeful in identifying and avoiding reorientalist representations, her rejection of abjection and victimhood, and her overt celebration of larger-than-life others, may have subverted the inferiorizing of the other, without, however, decreasing the process of othering.